Relationship Between Patients with Hypertension Stage 2 and Chronic Kidney Disease (CKD) at Harapan Keluarga Hospital - Octivani, Fania; Arsatt, Maz Isa Ansyori; Maulana, Akhada; Wedayani, Anak Agung Ayu Niti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hypertension and chronic kidney disease (CKD) are interrelated global health challenges with rising prevalence, particularly in low-resource settings such as Indonesia. This retrospective cohort study aimed to investigate the association between hypertension stage 2 and CKD among 65 patients treated at Harapan Keluarga Hospital between 2023 and 2024. Data were obtained through medical record reviews, and statistical analysis was conducted using Chi-square testing and odds ratio (OR) calculations. A significant association was found between stage 2 hypertension and CKD (p = 0.001), although the OR value of 0.888 (95% CI: 0.821–0.920) suggests a negative correlation, potentially influenced by variations in treatment adherence, demographic characteristics, or other confounding factors. Differences in BMI and blood pressure between male and female patients were also observed, highlighting the role of sex-specific physiological and lifestyle variables in disease progression. The findings emphasize the importance of tailored clinical management strategies for hypertensive patients to prevent CKD progression, particularly in healthcare settings with limited diagnostic and therapeutic resources.